The Effect of Individual Characteristics on the Performance of Primary School Teachers in Bone District, Bone Regency of South Sulawesi, Indonesia - Hamzah, Firman; Asriadi; M. Awaluddin; Siraj, Muhammad Lutfi; Santos, Hezron Alhim Dos (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2020)
Efforts to improve the quality of education in schools occur when teacher performance increases optimally. The purpose of this research is to describe individual characteristics, teacher performance descriptions, on teacher performance. The method used in this research is the quantitative descriptive method with an associative approach. The study population was teachers in elementary schools (SD) in Awangpone District, Bone Regency, totaling 30 schools with a total of 233 teachers. The research sample consisted of 35 respondents and the sampling technique used random sampling techniques. The data collection techniques used in this study were: observation (observation), questionnaire (questionnaire), interviews, and documentation. The data analysis technique used in this research is the descriptive statistical analysis technique and inferential statistical analysis technique which aims to examine the research variables. Based on the results of the study, the level of personal characteristics was assessed as good, teacher performance was considered good, and there was an influence between personal characteristics on the performance of elementary school teachers in Awampone District, Bone Regency. shows the R square value of 41.90 percent. This means that other factors contribute 59.10 percent to teachers’ performance.